Engaging the Ethiopian Knowledge Diaspora - Woldegiyorgis, Ayenachew A. (International Higher Education, 2019)
Although there is a consensus that Africa has considerable intellectual resources in its diaspora, the benefit that the continent is garnering from it is limited for different reasons. The political climate in several countries and the absence of well-articulated strategies are among the main factors preventing the African knowledge diaspora from engaging with their home countries. Even when, occasionally, political relations improve—such as currently in Ethiopia, diaspora engagement in higher education is challenged by routine issues such as bureaucratic processes, the absence of a coordinating body, and a mismatch between demand and supply.